PAI-1 Synthesis in the Human Hepatoma Cell Line Hep G2 Is Increased by Cytokines - Evidence that the Liver Contributes to Acute Phase Behaviour of PAI-1 - de Boer, J P; Abbink, J J; Brouwer, M C; Meijer, C; Roem, D; Voorn, G P; Lambers, J W J; van Mourik, J A; Hack, C E (Thrombosis and Haemostasis, 1991)
The acute phase behaviour of the fast inhibitor of tissue-type plasminogen activator (PAI-1) in vivo has been attributed to increased synthesis by endothelial cells. However, most other acute phase proteins in vivo are synthesized in the liver, which process is regulated by cytokines and can be studied in the hepatoma derived cell line HepG2.In this study, we investigated whether the synthesis of PAI-1 by HepG2 cells is regulated by the cytokines recombinant IL-1, rlL-6 and rTNF. Recombinant IL-1 and rTNF each increased PAI-1 synthesis by Hep G2 cells two to three fold, whereas rIL-6 hardly had an effect. Mixtures of rIL-1, rIL-6 and rTNF increased PAI-1 synthesis up to eleven fold. The effects observed were not due to non-specific effects on Hep G2 cell metabolism, since synthesis of alpha-2-antiplasmin was not effected by any of those cytokines, whereas fibrinogen synthesis was increased three to four fold by rIL-6, but was unaffected by rIL-1. Thus, our results demonstrate that synthesis of PAI-1 by Hep G2 cells is regulated by cytokines and implicate that the acute phase behaviour of PAI-1 in vivo at least in part may be due to an increased synthesis by the liver.